(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Among elderly gynecological patients with concomitant cardiovascular diseases, anesthesia management represents a high-risk challenge due to the susceptibility of this group to intraoperative hemodynamic instability. Combined spinal-epidural anesthesia (CSEA) offers significant advantages by providing reliable analgesia, reducing systemic drug requirements, and minimizing cardiovascular stress. In this study, we analyzed 30 patients aged 60–80 years undergoing hysterectomy under CSEA. Our findings demonstrated that intrathecal administration of 10 mg of 0.5% bupivacaine combined with epidural fentanyl resulted in mild and transient decreases in blood pressure and heart rate, stabilizing within 20–30 minutes. Compared to general anesthesia, CSEA provided superior hemodynamic stability and fewer cardiovascular complications. This paper further discusses the clinical significance of CSEA in elderly patients, comparing our results with international studies and guidelines.